Bank profitability in the euro area in times of high inflation - Mislav Brkić (Public Sector Economics)
Following the shift in the European Central Bank's (ECB) monetary policy in mid2022, the interest income of euro area banks rose markedly, boosting their overall profitability. This paper shows that the positive impact of higher interest rates on bank profitability was amplified by the existence of abundant excess liquidity. In particular, since euro area banks held large stocks of excess liquidity, they were able to earn substantial risk-free interest income by simply putting their liquidity into the ECB’s deposit facility. In addition, due to the prolonged period of monetary expansion and zero interest rates on time deposits, the share of overnight deposits in total bank liabilities had increased significantly by the time the ECB tightened its policy. Since overnight deposits typically respond slowly to policy rate changes, such a structure of funding enabled euro area banks to enjoy comfortable net interest margins for some time.